61.5k views
1 vote
Write an equivalent expression by applying the distributive property (x + y + 3) x (y + 1) = A: 2y2+xy+4 B: 2y + x + 4 C: y2+xy+4y+x+3 Please help math makes me go insane

2 Answers

5 votes


(x+y+3)\cdot(y+1)=\\\\=(x+y+3)\cdot y+(x+y+3)\cdot1=\\\\=xy+y^2+3y+x+y+3=\\\\=\boxed{y^2+xy+4y+x+3}

Answer C.

User Jonatan Goebel
by
5.4k points
4 votes

Answer:

C

Explanation:

So we have the expression:


(x+y+3)*(y+1)

To multiply, use the distributive property. Multiply (y+1) to each term on the left:


=x(y+1)+y(y+1)+3(y+1)

Distribute the variables:


=(xy+x)+(y^2+y)+(3y+3)

Rearrange them to combine like terms:


=y^2+xy+y+3y+x+3\\=y^2+xy+4y+x+3

The correct answer is C.

Edit: Typo

User Mangi Morobe
by
4.4k points